1+6x=4x-11

Simple and best practice solution for 1+6x=4x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+6x=4x-11 equation:


Simplifying
1 + 6x = 4x + -11

Reorder the terms:
1 + 6x = -11 + 4x

Solving
1 + 6x = -11 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
1 + 6x + -4x = -11 + 4x + -4x

Combine like terms: 6x + -4x = 2x
1 + 2x = -11 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 + 2x = -11 + 0
1 + 2x = -11

Add '-1' to each side of the equation.
1 + -1 + 2x = -11 + -1

Combine like terms: 1 + -1 = 0
0 + 2x = -11 + -1
2x = -11 + -1

Combine like terms: -11 + -1 = -12
2x = -12

Divide each side by '2'.
x = -6

Simplifying
x = -6

See similar equations:

| x+7x=7 | | fx=x^2+3 | | -0.1*x+60=25 | | 1-2x(5+x)=7 | | (x+4)(x-2)=112 | | 3u^2-75=0 | | Y^2-2y-13=0 | | 2a-5(a+1)=0 | | 3a+2a-a=24 | | x(x+5)-10=x^2-2x+4 | | 2b-7=21 | | h+5h-3-6h=0 | | 3-3n=-27 | | 10-8y+(-13)+12y+8-6y= | | 8(-8)+7y=56 | | 2(2x-6)+2(x+3)=24 | | 12m+9-2m-16=0 | | x+2=-34+5x | | 230=2(3x-5)+2(5x+8) | | 100(4+x)=.75(8+x) | | 59+x=59 | | 7x+2=4x+29 | | 6a+10b-a+b= | | 7=-3x+5x-1 | | 6b+3=45 | | (3x-y)(x+2y)= | | X+51=50 | | 2m+4m-m=75 | | 3+10x+3x^2=0 | | 50=6y+32 | | 57+x=85 | | 24x-8=8(3x-1) |

Equations solver categories